A Study of Nitrate Reductase Activity in the Populus deltoides Leaves - Pokhriyal, T. C.; Raturi, A. S. (Indian Forester, 1985)
The method for assay of in vivo nitrate reductase(NR) activity was standardised for poplar leaves. The maximium activity(mÎ¼ moles NO-3 reduced g fr, wt-1h-1)was obtained with a 0.05 m phosphate buffer of 7.6 pH and 0.05 m potassium nitrate concentration. Maximum NR activity and total activity(leaf)-1 was observed in the sixth leaf from the tip and further it decreased with the increase in age. An increase in the fresh and dry weights of leaves was observed upto eighth leaf. The middle order leaves seem to be more efficient in the rate of photosynthesis to gain higher fresh and dry weights and NR activity as compared to young and old ones.